2015
DOI: 10.1073/pnas.1417623112
|View full text |Cite
|
Sign up to set email alerts
|

FT-like proteins induce transposon silencing in the shoot apex during floral induction in rice

Abstract: Floral induction is a crucial developmental step in higher plants. Florigen, a mobile floral activator that is synthesized in the leaf and transported to the shoot apex, was recently identified as a protein encoded by FLOWERING LOCUS T (FT) and its orthologs; the rice florigen is Heading date 3a (Hd3a) protein. The 14-3-3 proteins mediate the interaction of Hd3a with the transcription factor OsFD1 to form a ternary structure called the florigen activation complex on the promoter of OsMADS15, a rice APETALA1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 65 publications
3
81
1
Order By: Relevance
“…This is consistent with previous data showing that many TE genes are transcriptionally active in maize shoot meristems (Ohtsu et al, 2007;Li et al, 2010;Martínez and Slotkin, 2012). In particular, a recent work showed that many TEs are transcribed in rice vegetative and reproductive shoot apex (Tamaki et al, 2015). The mechanism of release of the TE silencing in meristems is not clear.…”
Section: H3k27me3 Is Dynamically Regulated During the Sam-to-im Transsupporting
confidence: 90%
“…This is consistent with previous data showing that many TE genes are transcriptionally active in maize shoot meristems (Ohtsu et al, 2007;Li et al, 2010;Martínez and Slotkin, 2012). In particular, a recent work showed that many TEs are transcribed in rice vegetative and reproductive shoot apex (Tamaki et al, 2015). The mechanism of release of the TE silencing in meristems is not clear.…”
Section: H3k27me3 Is Dynamically Regulated During the Sam-to-im Transsupporting
confidence: 90%
“…Under inductive photoperiods, both Hd3a and RFT1 are transcribed, and their protein products are essential for flowering to the extent that artificial reduction of their mRNA expression results in never-flowering plants (Komiya et al, 2008;Tamaki et al, 2015). However, transcription of RFT1 can be induced also under long days (LDs), and its floral promotive activity under these conditions contributes to the facultative nature of the photoperiodic flowering response of rice (Gómez-Ariza et al, 2015;Komiya et al, 2009).…”
Section: Both Proteins Share Homology With Flowering Locus T (Ft) Ofmentioning
confidence: 99%
“…Transcription of Ehd1, Hd3a, and RFT1 thus correlates under SD in leaves, showing a transient induction that persists only for the time required to irreversibly commit flowering at the SAM (Galbiati et al, 2016;Doi et al, 2004;Cho et al, 2016;Komiya et al, 2008). Once a sufficient amount of Hd3a and/or RFT1 proteins reaches the SAM, expression of target genes that promote inflorescence formation is induced (Taoka et al, 2011;Tamaki et al, 2015).…”
Section: Both Proteins Share Homology With Flowering Locus T (Ft) Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies in higher plants, most transferred DNA (T-DNA) containing sequences homologous to the endogenous target gene was found to have integrated randomly into the plant genome through the nonhomologous end joining (NHEJ) pathway, leading to decreased GT frequency (0.01%-0.1% compared with random integration; Paszkowski et al, 1988;Offringa et al, 1990;Puchta et al, 1996). More recently, GT has developed to become a reproducible and general approach, at least in rice (Oryza sativa), through the use of a positive-negative selection system with the hygromycin resistance gene as a positive selection marker and the diphtheria toxin A subunit (DT-A) gene as a negative selection marker (Terada et al, 2002(Terada et al, , 2007Yamauchi et al, 2009;Moritoh et al, 2012;Ono et al, 2012;Ozawa et al, 2012;Dang et al, 2013;Tamaki et al, 2015). Toxic to rice plants, expression of DT-A is also toxic in some dicots, such as Arabidopsis (Arabidopsis thaliana; Czakó et al, 1992; Thorsness et al, 1993;Day et al, 1995;Nilsson et al, 1998;Tsugeki and Fedoroff, 1999;Weijers et al, 2003), tobacco (Nicotiana tabacum; Czakó et al, 1992;Day et al, 1995;Twell, 1995;Uk Kim et al, 1998), and Brassica campestris (Lee et al, 2003).…”
mentioning
confidence: 99%